Analysis of Facebook Social Media Utilization in Shaping the Positive Image of Regional Leaders and Disseminating Government Programs (A Case Study) - Redemptus Darus Triusada; Yusmanizar Yusmanizar; Alem Febri Sonni (Journal of Public Representative and Society Provision, 2026)
This study aims to analyze the utilization of Facebook as a social media platform in shaping the positive image of regional leaders and disseminating government programs, with a case study conducted at the Protocol and Leadership Communication Division of the Nunukan Regency Secretariat. The research was conducted through qualitative descriptive methods, involving observations, interviews, and documentation. Data were collected from six informants from the Nunukan Regency Government. The findings show that the use of Facebook by the Protocol and Leadership Communication Division has been an effective strategy in both building a positive public image of the regional head and serving as a communication channel to disseminate information about government programs to the public. This study concludes that Facebook plays a significant role as a media tool for regional government public relations efforts, particularly in enhancing public perception and improving the reach of official communications.